The microhabitat distribution of two Dactylogyrus species parasitizing the gills of the barbel, Barbus barbus - Kadlec, D; Simková, A; Gelnar, M (Journal of helminthology, 2003)
The microhabitat distribution of two congeneric species Dactylogyrus carpathicus and D. malleus (Monogenea) parasitizing the gills of the barbel (Barbus barbus L.) was investigated. We tested whether congeneric species exhibited microhabitat preference and whether interspecific interactions could be attributed to the microhabitat segregation of congeners. The outlying mean index method was used to evaluate species microhabitats. Gill variables (different microhabitats within gills) were used as environmental factors characterizing the gills. When abundances of both species were highest, and no significant difference was found between the abundance of the two species, the gill segments and gill areas were the most important factors segregating the Dactylogyrus species on the gills. Niche overlap was low within each of the four gill arches, and parasites were segregated in the same microhabitats within each gill arch. When abundances of both species were low, each monogenean species was segregated at the level of the gill arches. When abundances of both species increased, the niche and overlap between species increased. The distribution of both congeneric species confirmed microhabitat preference within the gills. The results suggest that microhabitat preference is dependent on species abundances, species being segregated in the case of low abundance, possibly to increasing mating opportunities. Both niche and overlap between species increased with species abundance. In the case of the high abundance of both species, microhabitat preference seems to be related to interspecific interactions between monogenean species, as previously found for endoparasitic species.
Keywords: nemoci ryb; Gills; biometrie; druhová specificita; Fish Diseases; Ecosystem; prevalence; Trematoda; Host-Parasite Interactions; Trematode Infections; žábry; tělesná konstituce; infekce červy třídy Trematoda; zvířata; Rakousko; Biometry; Body Constitution; Austria; roční období; Seasons; Species Specificity; Prevalence; Animals; interakce hostitele a parazita; ekosystém; Cyprinidae